The Formality of Speech Styles on “Breakout” Music Program by Hosts in NET TV - Masluchah Masluchah; Mochamad Nuruz Zaman (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2018)
This research aims to find speech styles on the Breakout music program by hosts in Net TV. The researcher is interested in doing a research about speech styles in the Breakout music program special Paramore because the speakers in the music program use speech styles when use communication with other people. The research questions in this research are the kinds of speech styles by male and female hosts and the differences between male and female of the speech style used hosts utterance on Breakout Music Program in Net TV. In the research, the researcher uses qualitative design. The finding of this research is the kinds of speech styles by male and female hosts that are found in Breakout Music Program special Paramore which classifies into five styles those are frozen style, formal style, consultative style, casual style and intimate style. The finding about differences between male and female of the speech styles used hosts utterance on Breakout Music Program. In the Conclusion, male hosts utterance data contains sixteen data involve in consultative style, forty-three data involve in casual style and five data involves in intimate style and female hosts utterance data contains twelve data involve in consultative style, twenty-eight data involve in casual style and six data involves in intimate style. Both male and female have three speech styles, but male is more in the third finding, while female also has three speech styles but it just a little.